Macroscopic lithotype characterisation of the 1st Middle-Polish (1st Lusatian) Lignite Seam in the Miocene of central Poland - Widera, Marek (Wydawnictwo Naukowe UAM, 2012)
The 1st Middle-Polish (1st Lusatian) Lignite Seam is exploited in open-cast mines in central Poland. A large number of lignite lithotypes, grouped in four lithotype associations, are distinguished: xylitic, detritic, xylo-detritic and detro-xylitic lithotype associations, which show various structures. Each lithotype association was produced under specific peat-forming environmental conditions. In the case of the lignite seams under study they represent all the main envi -ronments that are known from Neogene mires, i.e.: fen or open water, bush moor, wet forest swamp and dry forest swamp. For a simple and practical description in the field of both the lignite sections and borehole cores, a new codification for lignite lithotypes is proposed. It is based on the codification of clastic deposits (lithofacies). The practical value of the new lignite lithotype codification is examined in three vertical sections of the 1st Middle-Polish Lignite Seam.
Keywords: Lignite lithotypes; Sedimentology; First Middle-Polish Lignite Seam; Miocene; Central Poland